Review of sour cassava starch production in rural Colombian areas - Zakhia, N.; Dufour, D.; Chuzel, G. [UNESP]; Griffon, D. (My University, 1996)
Sour cassava starch is traditionally produced in Latin America for preparation of cheesebreads such as 'pan de yuca' and 'pandebono' in Colombia, and 'pao de queijo' in Brazil. The processing involved is described and improvements suggested. Criteria for quality assessment of sour cassava starch are based on consumers' requirements. Recommendations are made for improving the processing and product quality. Alternatives are given for extending the potential value of this traditional foodstuff.
Keywords: breadmaking; cassava; Colombia; equipment; small-scale processing; socioeconomics; starch; Manihot esculenta